2010
DOI: 10.1200/jco.2008.20.2267
|View full text |Cite|
|
Sign up to set email alerts
|

Role of Cancer Treatment in Long-Term Overall and Cardiovascular Mortality After Childhood Cancer

Abstract: This study is the first, to our knowledge, to establish a relationship between the radiation dose received by the heart during radiotherapy for a childhood cancer and long-term cardiac mortality. This study also confirms a significant excess risk of cardiac mortality associated with a high cumulative dose of anthracyclines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
265
2
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 403 publications
(284 citation statements)
references
References 38 publications
10
265
2
5
Order By: Relevance
“…23,24 Mediastinal irradiation and higher dose of anthracycline administration have been described as critical risk factors for the development of numerous cardiac complications. [25][26][27] In line with these observations, especially early onset HL survivors stood out with the highest SMRs due to cardiovascular death causes (SMR 9.2, 95% CI 3.8-14.5 and SMR 5.0, 95% CI 3.8-6.3 for childhood and YA survivors, respectively). Furthermore, the concomitant therapy with herceptin, cyclophosphamide, bleomycin, vincristine, amsacrine, mitoxantrone may contribute to an elevated risk for cardiotoxicity.…”
Section: Epidemiologysupporting
confidence: 71%
See 1 more Smart Citation
“…23,24 Mediastinal irradiation and higher dose of anthracycline administration have been described as critical risk factors for the development of numerous cardiac complications. [25][26][27] In line with these observations, especially early onset HL survivors stood out with the highest SMRs due to cardiovascular death causes (SMR 9.2, 95% CI 3.8-14.5 and SMR 5.0, 95% CI 3.8-6.3 for childhood and YA survivors, respectively). Furthermore, the concomitant therapy with herceptin, cyclophosphamide, bleomycin, vincristine, amsacrine, mitoxantrone may contribute to an elevated risk for cardiotoxicity.…”
Section: Epidemiologysupporting
confidence: 71%
“…6,7 However, the cancer survivors as well as siblings were more likely to die from other death causes compared to the general population (SMR 2.7, 95% CI 2.3-3.1 among all cancer survivors and SMR 1.7, 95% CI 1.5-1.8 among siblings, respectively) like in earlier studies. 4,7,11,25 We chose a sibling cohort as another reference group to reduce the influence of genetic and environmental confounders when analyzing the effects of cancer and its therapy on late mortality. The markedly higher SMR due to other death causes among cancer survivors compared to siblings supports the selection of the sibling cohort to lower the impact of confounders in our analysis.…”
Section: Epidemiologymentioning
confidence: 99%
“…The mechanisms relevant for lower doses are likely to differ from those relevant at higher (e.g., radiotherapeutic) doses. However, risks in studies of medically-exposed groups, with relevant organ doses usually well above 0.5 Gy, are generally consistent with those in populations exposed at the much lower doses and dose rates discussed above [3][4][5][6]44], suggesting that mechanisms operating at high doses and high dose rates may be similar to those at low doses and dose rates. The fact that the IHD risks using mean heart dose in these high-dose/partial-body exposed groups are similar to the risks in the generally uniformly whole-body-exposed groups using whole-body dose discussed above ( Table 7) also suggests that mean dose to the heart is the most relevant metric for predicting radiation-associated IHD [44].…”
Section: Discussionmentioning
confidence: 55%
“…Therapeutic doses of ionizing radiation to the heart and large arteries are associated with various types of circulatory disease [3][4][5][6]. More recently, and controversially, studies on several groups exposed to low-to-moderate doses of radiation have reported excess mortality and morbidity from circulatory diseases, in particular the Life Span Study (LSS) of Japanese atomic bomb survivors [7] and several occupationally exposed cohorts [8].…”
Section: Introductionmentioning
confidence: 99%
“…Such studies have the merit of following up large cohorts of patients treated for different tumors with different therapies in different periods of time. They usually rely on information through national health registries [11,16]. Causes of death are consequently grouped according to general classifications, that is, diseases of the cardiovascular or respiratory system, making it impossible to go into more detail.…”
Section: Discussionmentioning
confidence: 99%